Некоторые вопросы обеспечения продовольственной безопасности в Республике Казахстан (Journal of actual problems of jurisprudence, 2019)
In this article the author examines some aspects of food security in Kazakhstan. Development of the agricultural sector in Kazakhstan is an important segment of the food security and further development of productivity in agriculture is the country’s major socioeconomic and political role.